Rapid eye movement sleep behavior disorder in Parkinson's disease: Magnetic resonance imaging study. Issue 6 (28th February 2013) - Ford, Andrew H.; Duncan, Gordon W.; Firbank, Michael J.; Yarnall, Alison J.; Khoo, Tien K.; Burn, David J.; O'Brien, John T.
ABSTRACT Background Rapid eye movement sleep behavior disorder has poor prognostic implications for Parkinson's disease. The authors recruited 124 patients with early Parkinson's disease to compare clinical and neuroimaging findings based on the presence of this sleep disorder. Methods The presence of rapid eye movement sleep behavior disorder was assessed with the Mayo Sleep Questionnaire. Magnetic resonance imaging sequences were obtained for voxel‐based morphometry and diffusion tensor imaging. Results Patients with sleep disorder had more advanced disease, but groups had similar clinical characteristics and cognitive performance. Those with sleep disorder had areas of reduced cortical grey matter volume and white matter changes compared with those who did not have sleep disorder. However, differences were slight and were not significant when the analyses were adjusted for multiple comparisons. Conclusions Rapid eye movement sleep behavior disorder was associated with subtle changes in white matter integrity and grey matter volume in patients with early Parkinson's disease. © 2013 Movement Disorder Society